Risk Factors of Intrauterine Fetal Death in Cipto Mangunkusumo General Hospital, Indonesia - Indarti, Junita; Mardhatillah, Syifa; Alda, Kristian; Vitasatria, Arresta; Solihin, Affan; Sumulyo, Ganot; Ikhsan, Muhammad; Agassi Antoniman, Mohammad (Syntax Corporation Indonesia, 2024)
Intra Uterine Fetal Death ( IUFD ) results from various disorders of the mother, fetus, and placenta. This study aimed to explore factors contributing to IUFD, knowing the risk factors will prevent this case in the future time. In 2016-2018, patients diagnosed with IUFD at 22 weeks of gestation were included. One hundred twenty-five patients with IUFD and 125 controls with alive fetuses were enrolled. Data were collected from the medical records of participants. Factors that may have contributed to IUFD were explored. Comparisons between various risk factors and outcomes of the two groups were made. P-value was statistically significant if ≤0.05. We found several factors that contribute to IUFD. Some factors like BMI, ANC provider, referred from tertiary health facility, and congenital anomaly increased the risk of IUFD by 2.86, 5.86, 6.26 and 9.45 times respectively. In contrast, some factors like a number of ANC ≥ 6 times and gestational age >36 weeks decrease the risk of IUFD. Regular and intensive ANC ≥ 6 times during pregnancy, number of pregnancy and gestational age ≥ 36 weeks significantly decreases the risk of IUFD with OR 0.12, 0.4, and 0.23 respectively. High-quality ANC to identify IUFD risk factors may lead to a significant decrease in its occurrences. Some factors like BMI, ANC provider, referred from tertiary health facility, and congenital anomaly increased the risk of IUFD, but Number of ANC≥ 6 times, number of pregnancy ≥2 and gestational age ≥36 weeks can reduce risk of IUFD.